Anatomy of hypothalamic and diencephalic nuclei involved in seasonal fertility regulation in ewes - Merchán, Miguel; Coveñas, Rafael; Plaza, Ignacio; Abecia, José Alfonso; Palacios, Carlos (Frontiers in Veterinary Science, 2023)
In this study, we describe in detail the anatomy of nuclei involved in seasonal fertility regulation (SFR) in ewes. For this purpose, the intergeniculate leaflet of the visual thalamus, the caudal hypothalamic arcuate nucleus, and suprachiasmatic, paraventricular and supraoptic nuclei of the rostral hypothalamus were morphometrically and qualitatively analyzed in Nissl-stained serial sections, in the three anatomical planes. In addition, data were collected on calcium-binding proteins and cell phenotypes after immunostaining alternate serial sections for calretinin, parvalbumin and calbindin. For a complete neuroanatomical study, glial architecture was assessed by immunostaining and analyzing alternate sections for glial fibrillary acidic protein (GFAP) and ionized calcium-binding adapter molecule 1 (IBA1). The results showed a strong microglial and astroglia reaction around the hypothalamic nuclei of interest and around the whole 3rd ventricle of the ewe brain. Moreover, we correlated cytoarchitectonic coordinates of panoramic serial sections with their macroscopic localization and extension in midline sagittal-sectioned whole brain to provide guidelines for microdissecting nuclei involved in SFR.